THE INFLUENCE OF GOOD CORPORATE GOVERNANCE, INTANGIBLE ASSETS, AND SALES GROWTH ON FINANCIAL DISTRESS IN MANUFACTURING FIRMS LISTED ON THE INDONESIA STOCK EXCHANGE DURING THE 2022–2024 PERIOD - Muhammad Daffa Zulfikar; Della Andriyani Ridwan; Efrina Surya Eningsih Silalahi (RADJA PUBLIKA, 2025)
This study investigates the determinants of financial distress in companies, emphasizing the roles of good corporate governance, intangible assets, sales growth, leverage, and liquidity. The research aims to provide empirical evidence on how these variables influence a firm’s likelihood of experiencing financial difficulties. A quantitative research approach was adopted, utilizing secondary data from annual reports of publicly listed companies over a defined observation period. Multiple regression analysis was applied to test the hypotheses, supported by classical assumption tests to ensure model validity. The results reveal that the size of the board of directors, the size of the board of commissioners, the presence of an effective audit committee, and managerial ownership significantly contribute to reducing financial distress. Sales growth was also found to have a positive effect on financial stability by strengthening operational performance and debt repayment capacity. Conversely, intangible assets showed no significant impact, while leverage exhibited a negative effect, indicating that debt structure management plays a critical role in distress prevention. Liquidity positively affected the ability to meet short-term obligations, reinforcing its importance in maintaining financial health. Overall, the findings highlight the interplay between governance mechanisms, operational growth, and financial structure in mitigating financial distress.